Synchronization of eostrus in goats with prostoglandin F 2α and progestin map - ΚΑΡΑΠΑΝΝΙΔΗΣ Α.; ΤΣΑΚΑΛΩΦ Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
During the goat breeding season, 45 cyclic does, aged between 2 to 5 years, were divided into two groups A and Β of 20 and 25 animals, respectively. These animals were on the 4-16th day of their cycle. The 20 does of group A were injected IM with 15 mg prostaglandin F (Panacelan). Oestrus was manifested in 90.0% of the does within 4 days after treatment. Blind inseminations performed on the 3rd and 4th day after the treatment resulted in a satisfactory pregnancy rate (77.8%). The 25 does of group Β were treated with intravaginal sponges, impregnated with 50 mg MAP (Veterdif) for a period of 16 days. Oestrus was manifested in 20 out of 22 does (90.9%) within 4 days after the withdrawl of sponges. Blind inseminations performed on the 2nd and 3rd day after the treatment resulted in a low pregnancy rate (55.0%). It is concluded that the use of prostaglandin FQ may be a useful means for achieving oestrus synchronization and satisfactory fertility in goats.